The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1186/1471-2164-11-302
|View full text |Cite
|
Sign up to set email alerts
|

Towards a membrane proteome in Drosophila: a method for the isolation of plasma membrane

Abstract: BackgroundThe plasma membrane (PM) is a compartment of significant interest because cell surface proteins influence the way in which a cell interacts with its neighbours and its extracellular environment. However, PM is hard to isolate because of its low abundance. Aqueous two-phase affinity purification (2PAP), based on PEG/Dextran two-phase fractionation and lectin affinity for PM-derived microsomes, is an emerging method for the isolation of high purity plasma membranes from several vertebrate sources. In c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 48 publications
2
17
0
1
Order By: Relevance
“…A proteomic study of Drosophila membrane proteins identified CG14509 as a membrane protein (Khanna et al 2010), consistent with its two predicted transmembrane domains. Though the protein bears no significant homology to vertebrate proteins and the only recognizable domain, the EB domain (MarchlerBauer et al 2015), has no described function, jus clearly has importance in regulating neuronal excitability during Drosophila development.…”
Section: Discussionmentioning
confidence: 77%
“…A proteomic study of Drosophila membrane proteins identified CG14509 as a membrane protein (Khanna et al 2010), consistent with its two predicted transmembrane domains. Though the protein bears no significant homology to vertebrate proteins and the only recognizable domain, the EB domain (MarchlerBauer et al 2015), has no described function, jus clearly has importance in regulating neuronal excitability during Drosophila development.…”
Section: Discussionmentioning
confidence: 77%
“…3a ) Meigo in Drosophila S2 cells decorated an ER-like membranous structure. To confirm the ER localization of Meigo, we used OptiPrep density centrifugation 25 to isolate membrane fractions of the ER and Golgi apparatus. Meigo was predominantly accumulated in the fractions that contained Hsc3, an ER-resident chaperone (also known as GRP78/BiP; Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The iTRAQ-labeled peptides were resolved by two-dimensional liquid chromatography prior to matrix-assisted laser desorption and ionization (MALDI) time-of-flight (TOF) tandem mass spectrometry (MS/MS) as described previously (16,51). Briefly, the samples were separated into 15 strong cation exchange (SCX) fractions, each of which was separated on an LC-Tempo nanoflow and MALDI spotting system, resulting in a total of 370 spots per SCX fraction.…”
Section: Methodsmentioning
confidence: 99%